P-7521—a new irreversible opioid ligand - Jin Wen-qiao; Fan Li-qun; Chen Xin-jian; Chi Xin-jian (Acta Pharmacologica Sinica, 2016)
In the receptor binding assay, P-7521 was a potent opioid ligand which acted mainly on mu receptor. The relative affinity ratio at mu, delta and kappa sites was 66:8:1. The inhibitory effects of P-7521 were 1868 and 6060 times more potent than morphine on the electrically evoked contractions in guinea pig ileum and mouse vas deferens, respectively and were readily antagonized by naloxone and Mr2266. These results indicate that P-7521 acted on mu receptor in guinea pig ileum and mouse vas deferens. In rabbit vas deferens, the compound had no agonist activity, but could antagonize the inhibitory effect of U-50488 H, a kappa agonist, showing the antagonistic characterization was on kappa receptor. The dissociation of P-7521 binding to opioid receptor were very difficult in mu binding assay and bioassays.